Antecedents of mobile banking applications acceptance and usage and its consequence on financial behavior in Namibia - Nuunyango, Anna Nambahu Panduleni (Department of Information Systems, 2026)
Banking is no longer limited to the physical location of a branch. Nowadays, consumers can do banking from the comfort of their own places, anywhere and anytime. Mobile banking applications offer mobility, 24/7 availability, broad reach, convenience, and ease of use unlike traditional banking. Regardless of the numerous advantages that mobile banking applications offer, the adoption rate has not met expectations or reached the level of mobile phone penetration adoption rate in many Lower and Middle Income Countries (LMICs). The use of digital financial services such as mobile banking applications changes consumers' financial behavior. Poor financial habits can cause debt, stress, health issues, and strained relationships. Thus, it is important to understand the impact of using mobile banking applications on consumers' financial behavior, as well as the factors that influence the acceptance and use of mobile banking applications. The study employed the unified theory of acceptance and use of technology and extended it with concepts of financial literacy, branch distance, trust, perceived risk, and financial behavior. The research model that was constructed informed data collection, using an online survey of Nambian banking consumers. 254 useable responses were received and the model was empirically tested. Structural equation modeling (SEM) analysis revealed that effort expectancy, habit, and trust positively influence consumer intention to accept mobile banking applications and trust negatively influences perceived risk, while habit and behavioral intention positively influence the use of mobile banking applications. Additionally, results show that mobile banking application use positively influences financial behavior in Namibia, implying that their use can lead to more responsible financial behavior.